1994
DOI: 10.1038/nbt0594-500
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Tomato Plants Expressing the Tomato Yellow Leaf Curl Virus Capsid Protein are Resistant to the Virus

Abstract: The tomato yellow leaf curl virus (TYLCV) gene that encodes the capsid protein (V1) was placed under transcriptional control of the cauliflower mosaic virus 35S promoter and cloned into an Agrobacterium Ti-derived plasmid and used to transform plants from an interspecific tomato hybrid, Lycopersicon esculentum X L. pennellii (F1), sensitive to the TYLCV disease. When transgenic F1 plants, expressing the V1 gene, were inoculated with TYLCV using whiteflies fed on TYLCV-infected plants, they responded either as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 27 publications
4
68
0
3
Order By: Relevance
“…To produce the large amounts of TYLCV CP required for in vitro DNA binding experiments, the CP gene, V1, was subcloned from the full-length TYLCV genome (pTYH 19 ; Kunik et al, 1994) into the bacterial expression vector pET28 (Novagen). To this end, V1 was first cloned as a HindIII-BclI restriction fragment into pBR328 (Boehringer).…”
Section: Methodsmentioning
confidence: 99%
“…To produce the large amounts of TYLCV CP required for in vitro DNA binding experiments, the CP gene, V1, was subcloned from the full-length TYLCV genome (pTYH 19 ; Kunik et al, 1994) into the bacterial expression vector pET28 (Novagen). To this end, V1 was first cloned as a HindIII-BclI restriction fragment into pBR328 (Boehringer).…”
Section: Methodsmentioning
confidence: 99%
“…For the geminivirus tomato yellow leaf curl virus (TYLCV) Israel strain, Kunik et al (1994) observed a delay in the appearance of disease symptoms and subsequent recovery from symptoms in tomato plants expressing the TYLCV coat protein gene.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the members of this subgroup have bipartite genomes (DNAs A and B) and are transmitted by the whitefly Bemisia tabaci Gennadius. To date, seven reports of transgenic plants conferring resistance to geminivirus infection have been published (Stanley et al, 1990 ;Day et al, 1990 ;Frischmuth & Stanley, 1994 ;Stenger, 1994 ;Kunik et al, 1994 ;Hong et al, 1996 ;Noris et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These have been reviewed extensively (Beachy et al, 1990;Wilson, 1993;Lomonossoff, 1995;Beachy, 1997;Lecoq, 1997). CPMR against a ssDNA gemini virus has also been reported (Kunik et al, 1994) and work is still in progress to demonstrate CPMR against double-stranded (ds)DNA caulirnoviruses or badnaviruses. Recently, coat proteinmediated immunity (CPMI) has been reported against potato mop-top, a fungally-transmitted rod-shaped virus (PMTV) and it has been shown that CPMI completely protected CPtransformed Nicotiana benthamona plants against natural transmission of the virus by its fungal vector, Spongospora subterranea f. sp subterranea (Reavy et al, 1995;Arif et al, 1999).…”
Section: Pathogen-derived Resistance Strategies In Crop Protectionmentioning
confidence: 99%